Indirect Discrimination: Huduma Namba (Digital Identification) and the Plight of the Nubian Community in Kenya (Strathmore Law Review, 2022)
Years after Kenya’s independence, the Nubians in Kenya are yet to enjoy the status of being fully-fledged citizens in their country. This is due to a variety of factors including the government’s refusal to formally acknowledge them as citizens, and its reluctance to streamline the current vetting process despite the overwhelming proof of its shortcomings. The discriminatory approach in the issuance of Kenyan identity cards (IDs) through the vetting process on grounds of religion and ethnicity not only entrenches the social, political, and economic exclusion of Nubians in Kenya but is also prohibited under Article 27(4) of the Constitution as indirect discrimination. Without taking adequate steps to change the status quo, the Kenyan government has instead launched a new digital identification system whose enrolment requires citizens’ IDs. Despite the full roll-out being halted by the court on grounds of data protection concerns, the switch to the Huduma Namba system is nonetheless set to disproportionately affect the ability of Nubians to participate as Kenyan citizens and contribute to their ‘otherness’. Consequently, this paper argues that the mandatory operationalisation of the Huduma Namba system in Kenya will constitute indirect discrimination against the Nubian community. It conducts this assessment by discussing the moral wrongfulness of indirect discrimination and laying out the architecture of indirect discrimination law in Kenya.